2015
DOI: 10.7717/peerj.1378
|View full text |Cite
|
Sign up to set email alerts
|

Chemotaxis and degradation of organophosphate compound by a novel moderately thermo-halo tolerantPseudomonassp. strain BUR11: evidence for possible existence of two pathways for degradation

Abstract: An organophosphate (OP) degrading chemotactic bacterial strain BUR11 isolated from an agricultural field was identified as a member of Pseudomonas genus on the basis of its 16S rRNA gene sequence. The strain could utilize parathion, chlorpyrifos and their major hydrolytic intermediates as sole source of carbon for its growth and exhibited positive chemotactic response towards most of them. Optimum concentration of parathion for its growth was recorded to be 200 ppm and 62% of which was degraded within 96 h at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Similarly, metabolism independent chemotaxis has been also reported for different bacterial strains towards various toxic chemicals [ 41 , 44 , 45 ]. However, we are not sure whether this chemotaxis behavior is metabolically independent and/or dependent [ 40 , 42 ], although results presented in this study demonstrated that all three bacteria had the ability to degrade both SDZ and 2-aminopyrimidine. More experiments related to chemotaxis behavior of these bacteria for those substrates which these strains were not able to metabolize and/or transform will be needed to clarify the chemotactic mechanism.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, metabolism independent chemotaxis has been also reported for different bacterial strains towards various toxic chemicals [ 41 , 44 , 45 ]. However, we are not sure whether this chemotaxis behavior is metabolically independent and/or dependent [ 40 , 42 ], although results presented in this study demonstrated that all three bacteria had the ability to degrade both SDZ and 2-aminopyrimidine. More experiments related to chemotaxis behavior of these bacteria for those substrates which these strains were not able to metabolize and/or transform will be needed to clarify the chemotactic mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…There are reports on various bacteria having the ability of chemotactic response towards various toxic pollutants such as nitroaromatics, organophosphate, chloroaromatics and aminobenzoates etc. [ 27 , 40 , 41 ]. In this study, SDZ-degrading bacteria such as Paracoccus sp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pailan and Saha (2015) reported a novel Pseudomonas sp. strain BUR11, moderately thermo-halo tolerant, was chemotactic to parathion and chlorpyrifos as well as degraded both pesticides [101]. Metabolism independent chemotaxis was observed for parathion by Pseudomonas sp.…”
Section: ) Pesticides and Herbicidesmentioning
confidence: 96%